Different Timing of Adjuvant Low Dose hCG and GnRH Agonist Trigger Protocol, in OHSS High-Risk Patient with Peak E2 Level <4000 pg/mL - Emilija Zoran Petanovska Kostova; Velentina Sotirovska; Gligor Dimitrov; Snezana Stojkovska; Makjuli Hadzi Lega; Daniela Stojanovska; Nikoleta Stamenkovska; Liljana Simjanovska; Zoranco Petanovski (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: The aim of the study is to compare the live birth rates between 1,500 I.U. of Human chorionic gonadotropin at the time of Gonadotropin-releasing hormone agonist trigger day or 35-36 h later on the oocyte pick-up day, without affecting the risk of significant ovarian hyperstimulation syndrome development in high-risk patients with peak E2 level <4,000 pg/mL